English teachers’ views about the communicative language approach: the case of Beitbridge urban schools. - Bhebhe, Khayelihle (Midlands State University, 2017)
This study sought to find out the teachers’ views about communicative language teaching within Beitbridge urban schools in Beitbridge District which is in Matabeleland South province. The researcher used the Qualitative research design. A sample of four schools was chosen using the purposive sampling method. Data in the field was collected using the in-depth interviews. Four teachers of English were interviewed using in-depth interviews. The collected data was analyzed both qualitatively and descriptively. The findings established that the Teachers of English language have negative views about communicative language teaching in some aspects but they generally view communicative language differently from the way the propounders of the approach did. The negative views have resulted in the teachers not fully implementing communicative language teaching approach in their lessons. The push to have a good pass rate has forced teachers to resort to the traditional ways like grammar-translation and natural way methods. Communicative language approach is viewed by the teachers as an approach that needs a lot of time to utilize hence it cannot be fully applied in the lessons. The researcher recommends that the Ministry of Primary and Secondary Education should launch workshops and seminars. Teachers of English should be innovative. ZIMSEC should come up with a new way of assessing pupils.